PENGARUH IDIOSINKRATIK (TRAIT ANALYSIS) GAYA KEPEMIMPINAN JOE BIDEN TERKAIT PEMBATALAN IZIN PROYEK PIPA MINYAK KEYSTONE XL PADA TAHUN 2021 - Septiana Nuraeni (2023)
The Keystone XL project is an oil pipeline project with the aim of transporting oil sands from the province of Alberta to refineries in the State of Texas. This project is considered a climate disaster which makes many parties oppose the development of this project. The dynamics of US politics also influenced this project, one of which was Joe Biden's decision to withdraw the permit for the construction of the Keystone XL oil pipeline. The study entitled "Idiosyncratic Influence (Trait Analysis) of Joe Biden's Leadership Style on the Policy of Canceling the Keystone Oil Pipeline Project Permit in 2021" reviews the characteristics of Joe Biden as the 46th President of the United States to determine the leadership style that influences the decision to remove permits from the oil pipeline project keystone xl. This research examines how Joe Biden's leadership style influences his decision regarding the cancellation of the Keystone XL oil pipeline project permit. This study uses a qualitative method using the Trait Analysis theory developed by Margaret G. Hermann. Trait analysis is carried out by analyzing Joe Biden's arrangement related to climate change in 2021. The results of the study use Hermann's 7 characteristics analysis, Joe Biden is a leader with the accommodative leadership style. This leadership style was influential in Joe Biden's policy regarding the keystone oil pipeline because Biden wanted to accommodate all stakeholders such as environmental activists, indigenous tribes, laborers, and other stakeholders. By rescinding the permit, Joe Biden is building a stronger relationship with them to achieve his energy, environment and labor goals.